Ancient Egyptian mummified shrews (Mammalia: Eulipotyphla: Soricidae) and mice (Rodentia: Muridae) from the Spanish Mission to Dra Abu el-Naga, and their implications for environmental change in the Nile valley during the past two millennia. (March 2021) - Woodman, Neal; Ikram, Salima
Abstract: Excavation of Ptolemaic Period (ca. 309–30 BC) strata within Theban Tombs 11, 12, -399-, and UE194A by the Spanish Mission to Dra Abu el-Naga (also known as the Djehuty Project), on the west bank of the Nile River opposite Luxor, Egypt, yielded remains of at least 175 individual small mammals that include four species of shrews (Eulipotypha: Soricidae) and two species of rodents (Rodentia: Muridae). Two of the shrews ( Crocidura fulvastra and Crocidura pasha ) no longer occur in Egypt, and one species ( Crocidura olivieri ) is known in the country only from a disjunct population inhabiting the Nile delta and the Fayum. Although deposited in the tombs by humans as part of religious ceremonies, these animals probably derived originally from local wild populations. The coexistence of this diverse array of shrew species as part of the mammal community near Luxor indicates greater availability of moist floodplain habitats than occur there at present. These were probably made possible by a greater flow of the Nile, as indicated by geomorphological and palynological evidence. The mammal fauna recovered by the Spanish Mission provides a unique snapshot of the native Ptolemaic community during this time period, and it permits us to gauge community turnover in the Nile valley of Upper Egypt during the last 2000 years. It also serves as a relevant example for understanding the extinction and extirpation of mammal species as effects of future environmental changes predicted by current climatic models.